Digital disruption: artificial intelligence and international trade policy. - Jones, Emily (Oxford Review of Economic Policy)
Digitalization of the global economy is occurring apace and has spurred a new wave of trade negotiations, as governments and technology firms vie to establish international rules and standards for the digital era. This article examines the ways that trade policy-makers are responding to artificial intelligence (AI), arguably the most disruptive of the new digital technologies. In a digitalized global economy, trade rules have implications for AI innovation, uptake, and governance, yet existing trade rules have significant shortcomings and need updating in order to assist with effective AI governance. Updating is happening but, so far, the changes focus on promoting AI and disproportionately reflect the interests of large technology firms, the major innovators and owners of AI. New digital trade rules include stringent intellectual property protections for source code and algorithms, and strong commitments to enable the free flow of data across borders. However, much less progress has been made in addressing cross-border risks and harms associated with AI, in areas such as competition policy; ethical, transparent, and accountable use of AI; personal data protection; and protections against the exploitative use of algorithms in consumer and labour markets.